2015
DOI: 10.1007/s11270-015-2642-9
|View full text |Cite
|
Sign up to set email alerts
|

Soil Dehydrogenases as an Indicator of Contamination of the Environment with Petroleum Products

Abstract: The aim of the research was to compare the effects of various petroleum products, biodiesel, diesel oil, fuel oil and unleaded petrol on soil dehydrogenases, and to evaluate biostimulation with compost and urea in the restoration of homeostasis of the soil contaminated with these products. The obtained results allowed for defining the weight of dehydrogenases in monitoring of the environment subjected to pressure from petroleum hydrocarbons. The studies were carried out under laboratory conditions for 180 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
64
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(74 citation statements)
references
References 35 publications
2
64
0
Order By: Relevance
“…Many authors reported that addition of spent engine oil to soil was stimulatory to the activity of dehydrogenase, but inhibitory to the activity of catalase (Achuba and Peretiemo-Clarke 2008, Achuba and Okoh 2014, Ramadass et al 2015. Kaczyńska et al (2015) showed that soil dehydrogenase is a good indicator of contamination of the environment with petroleum products. The increase of dehydrogenase activity could be due to the involvement of specific microorganisms in the metabolism of polyaromatic hydrocarbons, which The same letter means a homogenous group in the columns for an enzyme (P < 0.05) could serve as a carbon source for the microbial growth (Margesin et al 2000).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many authors reported that addition of spent engine oil to soil was stimulatory to the activity of dehydrogenase, but inhibitory to the activity of catalase (Achuba and Peretiemo-Clarke 2008, Achuba and Okoh 2014, Ramadass et al 2015. Kaczyńska et al (2015) showed that soil dehydrogenase is a good indicator of contamination of the environment with petroleum products. The increase of dehydrogenase activity could be due to the involvement of specific microorganisms in the metabolism of polyaromatic hydrocarbons, which The same letter means a homogenous group in the columns for an enzyme (P < 0.05) could serve as a carbon source for the microbial growth (Margesin et al 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Based on the activity of assayed soil oxidoreductases, indices of the spent engine oil and selenate effects were calculated using the following formulas (Kaczyńska et al 2015):…”
Section: Methodsmentioning
confidence: 99%
“…Based on the mean activity of assayed soil phosphatases, indices on effects of creosote and LMWOAs were calculated using the following formulas (Kaczyńska et al 2015): If IF=1, there is no influence of the tested factor on oxidoreductases. If IF<1, there is inhibition of the oxidoreductases activity by the tested factor and if IF>1, there is stimulation of the oxidoreductases activity by the tested factor (Stręk and Telesiński 2016a).…”
Section: Methodsmentioning
confidence: 99%
“…The contamination with crude oil increased the amount of total organic and water-soluble C. Some compounds within these fractions may serve as energy sources for microbial populations (Bastida et al, 2016). However, the level of BGA in Effect of wasterwater sludge application on enzyme activities in soil (Kaczyńska et al, 2015).…”
Section: Soil Enzyme Activitiesmentioning
confidence: 99%
“…The addition of N and P to oil-polluted soil accelerates the biodegradation of the petroleum in soil. In another research, it was proved that biosolid was useful in the biostimulation of soils contaminated with petroleum products (Kaczyńska et al, 2015).…”
Section: Soil Enzyme Activitiesmentioning
confidence: 99%